Choroidal vascular occlusion in a child with a connective tissue disease and complement C4 deficiency - Ghazi, Nicola G. (2002)
Objective To report the histopathologic findings in the eyes of a patient with a connective tissue disease and complement deficiency. Design Human postmortem ocular histopathologic study. Intervention A 15-year-old female died from complications of a connective tissue disease of uncertain etiology, particularly acute respiratory distress syndrome. Abnormalities seen in the eyes at autopsy were consistent with complement activation, granulocyte aggregation, and leukocyte embolization. Main outcome measures Both eyes were examined by light microscopy. Results Some choroidal vessels were occluded by platelet–fibrin thrombi and occasionally by aggregates of granulocytes and fibrin. Serous retinal detachment involving the macula and peripheral retina was present in both eyes. Conclusions This is a report of the ocular histopathologic findings in a patient with connective tissue disease and complement C4 deficiency. The light microscopy findings were consistent with complement activation with granulocyte aggregation and leukocyte embolization and may represent another mechanism to explain the clinical findings in patients with connective tissue disease, particularly systemic lupus erythematosus.